Early Results of Surgical Simultaneous Therapy for Significant Carotid Artery Stenosis and Heart Disease - Irqsusi, Marc; Vannucchi, Alessandro; Beckers, Julius; Kasseckert, Stefan; Waldhans, Stefan; Vogt, Sebastian; Moosdorf, Rainer G. H. (The Thoracic and Cardiovascular Surgeon, 2018)
Background The purpose of this single-center, retrospective study was to review the early outcome with defined endpoints of myocardial infarction, brain injury, and death after coronary bypass grafting and simultaneous carotid endarterectomy with or without combined valve replacement.Methods During the preoperative investigation 52 (44 males, 8 females) patients were examined by cardiac catheterization within the scope of their coronary status. In addition, all patients underwent echocardiography, CT angiography of the supra-aortic vessels, and full description of their neurologic status. Included were all patients with the need of coronary revascularization, valve disease, and either symptomatic or asymptomatic carotid artery stenosis with a maximal narrowing of >70%.Results There was one (2%) patient with a perioperative stroke and paresis of the upper limb. One (2%) patient experienced PRIND (2%). Eighteen (35%) patients suffered symptomatic transitory psychotic syndrome that fully recovered in all patients. One (2%) patient incurred a perioperative myocardial infarction that could be cured by percutaneous coronary stent implantation. Overall mortality was 4%.Conclusion Simultaneous coronary bypass grafting as a single procedure or in combination with valve replacement and endarterectomy of severe carotid lesions with or without patients' history of previous stroke can be performed with a calculated low surgical risk. The complication rate for neurologic and myocardial events is low compared with the hazard of a single surgical repair. The in-hospital mortality is not significantly different to isolated procedures. The concomitant appearance of coronary stenosis and carotid artery disease is reasonable due to the nature of arteriosclerosis. In our opinion these patients benefit from a combined surgical approach.
Keywords: carotid arteries; cardiopulmonary bypass; coronary artery bypass grafts surgery; coronary artery bypass grafting; neurology/neurologic (deficits disease injury); stroke